Can composite packaging and selective enamel etching affect the clinical behavior of bulk-fill composite resin in posterior restorations? 24-month results of a randomized clinical trial - Marcos de Oliveira BARCELEIRO; Chane TARDEM; Elisa Gomes ALBUQUERQUE; Leticia de Souza LOPES; Stella Soares MARINS; Luiz Augusto POUBEL; Roberta BARCELOS; Romina ÑAUPARI-VILLASANTE; Alessandro Dourado LOGUERCIO; Fernanda Signorelli CALAZANS (University of São Paulo, 2023)
Abstract Objectives This is a double-blind, split-mouth, randomized clinical study that aims to evaluate the influence of bulk-fill composite packaging presented in syringes (BSy) and capsules (BCa), and the effect of selective enamel etching (SEE) on the clinical performance of class I and II bulk-fill resin composite restorations after 24 months. Methodology A total of 295 class I or class II restorations were performed on 70 patients. One universal adhesive was applied in all restorations. SEE was used in 148 restorations and self-etching mode (SET) in 147 restorations. After the adhesive application, cavities were restored with Filtek Bulk-fill Posterior Restorative in syringes (BSy), Filtek One Bulk-fill in capsules (BCa), or Filtek Supreme Ultra in syringes with the incremental technique (In). All restorations were evaluated using the FDI criteria after one week and after six, 12, and 24 months. Kaplan-Meier survival analysis and Pearson's Chi-square test were used (α=0.05) for statistical analysis. Results After 24 months, 62 patients were evaluated and four restorations were lost due to fracture (one for SEEBSy, two for SEEIn, and one for SETIn). No significant differences in the fracture and retention rate were found between groups (p>0.05). SEE showed significantly fewer marginal adaptation defects than SET (p<0.05). BCa and BSy groups showed fewer marginal discrepancies compared to In (p<0.05). Restorations performed with BCa showed less color mismatch than BSy or In (p<0.05). Conclusion Although all restorations exhibited satisfactory clinical performance after 24 months of clinical service, the clinical behavior of class I and II restorations' improved when performed with a bulk-fill composite in capsules, mainly when associated with a universal adhesive applied with SEE.